-4(x+4)+9(2x-9)=13(x-8)-7

Simple and best practice solution for -4(x+4)+9(2x-9)=13(x-8)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+4)+9(2x-9)=13(x-8)-7 equation:


Simplifying
-4(x + 4) + 9(2x + -9) = 13(x + -8) + -7

Reorder the terms:
-4(4 + x) + 9(2x + -9) = 13(x + -8) + -7
(4 * -4 + x * -4) + 9(2x + -9) = 13(x + -8) + -7
(-16 + -4x) + 9(2x + -9) = 13(x + -8) + -7

Reorder the terms:
-16 + -4x + 9(-9 + 2x) = 13(x + -8) + -7
-16 + -4x + (-9 * 9 + 2x * 9) = 13(x + -8) + -7
-16 + -4x + (-81 + 18x) = 13(x + -8) + -7

Reorder the terms:
-16 + -81 + -4x + 18x = 13(x + -8) + -7

Combine like terms: -16 + -81 = -97
-97 + -4x + 18x = 13(x + -8) + -7

Combine like terms: -4x + 18x = 14x
-97 + 14x = 13(x + -8) + -7

Reorder the terms:
-97 + 14x = 13(-8 + x) + -7
-97 + 14x = (-8 * 13 + x * 13) + -7
-97 + 14x = (-104 + 13x) + -7

Reorder the terms:
-97 + 14x = -104 + -7 + 13x

Combine like terms: -104 + -7 = -111
-97 + 14x = -111 + 13x

Solving
-97 + 14x = -111 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-97 + 14x + -13x = -111 + 13x + -13x

Combine like terms: 14x + -13x = 1x
-97 + 1x = -111 + 13x + -13x

Combine like terms: 13x + -13x = 0
-97 + 1x = -111 + 0
-97 + 1x = -111

Add '97' to each side of the equation.
-97 + 97 + 1x = -111 + 97

Combine like terms: -97 + 97 = 0
0 + 1x = -111 + 97
1x = -111 + 97

Combine like terms: -111 + 97 = -14
1x = -14

Divide each side by '1'.
x = -14

Simplifying
x = -14

See similar equations:

| 6a+7=71 | | 3.5q-2.5-4.8q=-2.3q-3.7 | | 4(x+5)-3(t+2)=14 | | 5=1-p-2 | | n+12/4=n/16 | | x+0.20x=21500 | | 1.6x=16 | | x-6/9=1 | | 2m+3n=c | | 3(3.14)d=12(3.14) | | 9x-(x-3)=5x+3(x+1) | | 4a^2+a-15= | | 8s=-16 | | m/3.5=4.2 | | 24=6.28r | | 97-113=-8(-4y)-17(2y)+y | | -3x+5y=8 | | 5+6x-4=7x-4-4x | | x^2-24x+40=0 | | a(x-5)=2b+7a | | 3x+15=2(-x) | | x^2-10-6x= | | 80=5(6+r) | | =48x^2-200x+200 | | 1=1-4x+4 | | m+12/9=5/9 | | m^2=-35+12m | | -5(2b+1)+(11b-6)=0 | | 97-13=-8(-4y)-17(2y)+y | | 12-4*3= | | x^2+10-6x= | | 0.15x+0.10(280-x)=30.75 |

Equations solver categories